Marine mammals and windfarms: Effects of alpha ventus on harbour porpoises - Dähne, M.; Peschko, V.; Gilles, A.; Lucke, Klaus; Adler, S.; Ronnenberg, K.; Siebert, U. (2014)
© Springer Fachmedien Wiesbaden 2014. All rights are reserved.Offshore windfarms have the potential to affect marine mammal populations. For harbour porpoises, the threat considered most important is the influence of noise during the construction phase. Effects of the operational period that need to be considered can be either noise effects or effects due to alteration to the habitat where foundations were erected. Visual surveys and stationary acoustic monitoring showed a strong avoidance reaction during pile-driving while during the operational period results were inconclusive. In future, these impacts must be seen in a larger framework to predict the biological significance of cumulative effects.